Disseminated mucormycosis and necrotizing fasciitis in immune-compromised patients: two case reports. Issue 1 (January 2015) - Mugambi, Machoki S.; Theron, Andre; Cox, Sharon; Pillay, Komala; Millar, Alastair J.W.; Numanoglu, Alp
Abstract : We present two case reports of disseminated mucormycosis and necrotizing fasciitis in an immune-compromised patient. First, a 3-month-old with untreated HIV infection presented in septic shock with abdominal wall-necrotizing fasciitis. Laparotomy revealed extensive abdominal wall necrosis, bowel, liver, kidney and subsequent retroperitoneal, posterior diaphragm and inferior vena cava involvement. Second, a 3-year-old on chemotherapy for Burkitt's lymphoma presented with pancytopenia, sepsis, abdominal wall-necrotizing fasciitis and left lower limb ischaemia. At surgery, there was necrosis of the abdominal wall, the large bowel and the ureter and thrombosis of the iliac vessels. Histology in both cases showed necrosis with fungal invasion consistent with mucormycosis. Both patients suffered mortality. We discuss mucormycosis and review the literature regarding mucormycosis in immune-compromised paediatric patients.